Navigating through moral outrage: case study of Balenciaga’s crisis response strategies in scansis and the perception of public - Styrman, Ekaterina (2025)
This study aims to investigate a specific type of crisis named scansis, which was recently introduced by crisis communication researchers. Scansis, as a crisis type, differentiates itself by evoking strong moral outrage among the public (Coombs et al., 2018). This study seeks to understand scansis through a case study of the French luxury fashion brand Balenciaga and its two ad campaigns. The company's ad campaigns in November 2022 sparked negative conversations about the brand in both social and traditional media.